2021
DOI: 10.1039/d1gc00692d
|View full text |Cite
|
Sign up to set email alerts
|

Improving the photocatalytic H2 evolution activity of Keggin polyoxometalates anchoring copper-azole complexes

Abstract: Eliminating the use of precious metals as cocatalysts and using visible light are two important aspects in the field of photocatalytic H2 evolution with polyoxometalates (POMs) as photosensitizers. Here we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 67 publications
0
34
0
Order By: Relevance
“…As shown in Figure , these measurements show a hysteresis loop, indicating that both materials are mesoporous structures. , The calculated Brunauer–Emmett–Teller (BET) surface area of Ni–Mo–S–rGO-200-24-2 and Ni–Mo–S-200-24-2 are 23.43 and 13.13 m 2 ·g –1 , respectively. These mesoporous structures provide sufficient channels for the electrolyte diffusion and emission of H 2 bubbles. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure , these measurements show a hysteresis loop, indicating that both materials are mesoporous structures. , The calculated Brunauer–Emmett–Teller (BET) surface area of Ni–Mo–S–rGO-200-24-2 and Ni–Mo–S-200-24-2 are 23.43 and 13.13 m 2 ·g –1 , respectively. These mesoporous structures provide sufficient channels for the electrolyte diffusion and emission of H 2 bubbles. , …”
Section: Resultsmentioning
confidence: 99%
“…These mesoporous structures provide sufficient channels for the electrolyte diffusion and emission of H 2 bubbles. 20,22 Electrocatalytic HER Measurements. The electrochemical measurements were performed with a three-electrode cell, a graphite rod as counter electrode, and a saturated calomel electrode (SCE) as reference electrode in 1.0 M KOH.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyoxometalates (POMs), as metal-oxo clusters with rich structures and various properties, have been widely used in many fields such as electricity, optics, catalysis, and materials. 1–9 The combination of POMs as inorganic units and transition metal complexes (TMCs) can form a variety of structures. 10 Moreover, the selection of appropriate organic ligands is very important for the construction of POM–TMC structures.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, N-donor ligands containing pyridyl, tetrazole, and imidazole groups have become popular candidates in recent years, due to the fact that the multiple N-donors makes it possible for them to play active roles in the construction of versatile structures and stable POM-based frameworks. [26][27][28] Further, the design of amide derivative ligands containing multiple N/O sites enriched the structures and expanded the application of POM-based complexes. For instance, two Evans-type POMbased complexes constructed from two different bis-pyridinebis-amide ligands, synthesized by Li et al showed excellent catalytic oxidation performance.…”
Section: Introductionmentioning
confidence: 99%